Komunikasi Efektif Dengan Pendekatan Psikologi - Rima Ivana; Dewi Kurniawati (Jurnal Ilmiah Wahana Pendidikan, 2023)
Humans are social creatures who communicate every day. In the process, each individual has their own goals by communicating. To achieve this goal, it is necessary to learn how to communicate effectively. Psychology is a science that studies human psychology, with a communication psychology approach, the communicator will better recognize the characteristics of effective communication. In this journal it is explained that there are 5 characteristics of effective communication, namely 1) understanding, 2) pleasure, 3) influence on attitude, 4) better relationship, 5) action. This journal was created to explain how the science of communication psychology can help increase the effectiveness of communication so that the goals of communication carried out by individuals can be achieved. Achieving the purpose of a communication is a value that is often underestimated and considered easy but is actually difficult.